Pendidikan Agama Islam dan Pembangunan Karakter Siswa Sekolah Dasar: Studi Eksplorasi - Mokh. Iman Firmansyah; Cucu Surahman; Widia Lestari; Silmi Septiani; Muhamad Ridwan Sudaryat (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
In the midst of the government’s important agenda in building the nation’s character, a number of facts still show a bad and serious phenomenon among students. This study aims to explore and analyze the values in every aspect of PAI material in the competence domain and the relevance of its role to build the character of elementary school students (SD). This study chose an exploratory qualitative approach by the design of the inductive content analysis of the directed type and confirmed by the theory of character strength of the Appendix to Permendikbud 67/2013 on KD and the Curriculum Structure of SD/MI. The results of the study found that PAI in elementary schools the aspects of PAI material and the domain of competence were related and contributed to building students’ character strengths, which include: First, attitudes of love, confidence, obedience, and gratitude. Second, a literate character towards the material aspects of PAI (al-Quran, Hadith, Aqidah/Creed, Ibadah/Worship, Akhlaq/Morals, and Tarikh/Islamic History). Third, attitudes and behavior; academic skills, helping others, caring about cleanliness and pro-environment, sincere and patient, generous, trustworthy and unyielding, communicative, polite, and respectful. Elementary school has a strategic position and role, and recommends that PAI teachers pay attention to the transmission portion and age construct of students in building character so that they can choose the right learning model and strategy.